Arterial Ischemic Stroke as an Unusual First Manifestation of Parvovirus B19 Myocarditis in an Infant - Bhansali, Suneet A; Sahulee, Raj (Cardiology and Cardiovascular Medicine, 2020)
We report a 20 month-old male who presented with sudden-onset left hemiparesis who was found to have thromboembolism of intracardiac thrombi from severely diminished ventricular function due to parvovirus B19 myocarditis. The patient experienced resolution of his thrombi with unfractionated heparin, normalization of his ventricular function with inotropic support, and steady recovery from his stroke with physical and occupational therapy.